Medialabs. New Laboratories of Digital Humanities in Poland - Sołtysiak, Daniel (Free your mind: Reflections on language, literature and culture, 2022)
The article will present the theoretical contexts of the functioning of medialabs: the changes and search for contemporary humanities and the assumptions of the digital humanities paradigm. In the Polish context, the most important are the sources of inspiration by Western institutions and pioneering initiatives that initiate a wide discourse among academics. The historical perspective refers to the idea of DIY and the processes of bottom-up computerization of the country. Medialabs are interdisciplinary institutions with various directions of activity. The second part of the article will be focusing on to the assumptions and methodology of my research on Polish medialabs, and to the observations made so far. The aim of the project is to examine the current condition of Polish medialabs (Katowice, Gdańsk, Kraków). The project will show how the postulate of re-literalization of the humanities and implementation of the axioms of digital humanities in practice is developing in Poland.